Combating money laundering and terrorism financing: perspectives from maqasid al-shariah - Raja Alias, Raja Madihah; Mohd Yasin, Norhashimah; Ibrahim, Badruddin; Zul Kepli, Mohd Yazid (Emerald Publishing Limited, 2019)
Money laundering and terrorism financing are financial crimes which affect the economic stability and integrity of the country. In this respect, the relevant regulator has a duty to preserve and protect the financial stability of the country. This duty is in line with the concept of the protection of wealth (hifz al-mal) under the maqāsid al-Sharīʿah or higher objectives of Islamic law framework. The objective of this chapter is to examine the protection of wealth vis-á-vis money laundering and terrorism financing from the maqāsid al-Sharīʿah perspective. This study analyses the primary and secondary legal sources on the laws and regulations on anti-money laundering and counter financing of terrorism while also considering the primary and secondary sources of Islamic law. This study is significant as it makes an exploration of the maqāsid al-Sharīʿah perspectives and discusses the position of unlawful wealth that is acquired from the illicit gain of property from the abuse of money laundering and the financing of terrorist activities. This chapter suggests that Islamic law emphasises on the lawful ownership of wealth and prohibits a person from acquiring illicit wealth. This study will contribute towards the study on the deployment of maqāsid al-Sharīʿah, which is beneficial in safeguarding an individual action as well as the country’s commitment against abuse and misuse of wealth for financial crimes.